2020
DOI: 10.1128/aac.02200-19
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Changes of Klebsiella pneumoniae in Response to Colistin Treatment and crrB Mutation-Mediated Colistin Resistance

Abstract: Polymyxins are increasingly used as the critical last-resort therapeutic options for multidrug-resistant Gram-negative bacteria. Unfortunately, polymyxin resistance has increased gradually over the past few years. Although studies on polymyxin mechanisms are expanding, systemwide analyses of the underlying mechanism for polymyxin resistance and stress response are still lacking. To understand how Klebsiella pneumoniae adapts to colistin (polymyxin E) pressure, we carried out proteomic analysis of a K. pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…The authors identified a large amount of differentially expressed proteins that may contribute to mcr-1 -mediated antimicrobial resistance through regulation of glycerophospholipid metabolism, LPS biosynthesis and phosphoethanolamine substrate accumulation [ 94 ]. Additionally, to adapt to colistin stress, some proteins involved in the TCA cycle and pentose phosphate pathway were highly expressed in K. pneumoniae strains [ 97 ]. These recent advances in proteomics highlight significant metabolic pathways and suggest that the processes involved in the acquisition of the colistin response are related to energy, carbohydrate, and lipid metabolism [ 96 , 97 ].…”
Section: Exploitation Of Colistin Resistance: Methods and Challengmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors identified a large amount of differentially expressed proteins that may contribute to mcr-1 -mediated antimicrobial resistance through regulation of glycerophospholipid metabolism, LPS biosynthesis and phosphoethanolamine substrate accumulation [ 94 ]. Additionally, to adapt to colistin stress, some proteins involved in the TCA cycle and pentose phosphate pathway were highly expressed in K. pneumoniae strains [ 97 ]. These recent advances in proteomics highlight significant metabolic pathways and suggest that the processes involved in the acquisition of the colistin response are related to energy, carbohydrate, and lipid metabolism [ 96 , 97 ].…”
Section: Exploitation Of Colistin Resistance: Methods and Challengmentioning
confidence: 99%
“…Additionally, to adapt to colistin stress, some proteins involved in the TCA cycle and pentose phosphate pathway were highly expressed in K. pneumoniae strains [ 97 ]. These recent advances in proteomics highlight significant metabolic pathways and suggest that the processes involved in the acquisition of the colistin response are related to energy, carbohydrate, and lipid metabolism [ 96 , 97 ]. Thus, the inhibition of the metabolic process may potentially offer a way to overcome colistin resistance [ 97 ].…”
Section: Exploitation Of Colistin Resistance: Methods and Challengmentioning
confidence: 99%
“…This suggests that crrB also induces the arnBCADTEF operon ( Cheng et al, 2016 , 2018 ; Jayol et al, 2017 ; Jeannot et al, 2017 ). Additional studies have taken proteomic and transcriptomic approaches to better understand PR and the role of crrB and have supported the observation that CrrA/B activates the arnBCADTEF operon ( Sun et al, 2020 ; Ramos et al, 2016 ). They also suggest that CrrA/B may alter the expression of several carbon metabolism pathways, including gluconeogenesis and the tricarboxylic acid (TCA) cycle.…”
Section: Introductionmentioning
confidence: 91%
“…The CrrC protein can activate the expression of both arnBCADTEF operon and pmrC gene via the PmrA/PmrB TCS (through an unknown mechanism) [ 40 , 41 ]. CrrB can also induce the expression of arnBCADTEF operon through phoP/phoQ but it is currently unknown if CrrC plays a role in this activation process [ 42 ] ( Figure 3 ).…”
Section: Colistin Resistance Mechanisms In K Pneumoniaementioning
confidence: 99%
“…The wild-type CrrB seems to repress kexD , but upon genetic alterations such as those, it is able to induce kexD through CrrA. However, crrC is simultaneously transcribed with kexD hampering a direct association between colistin resistance and kexD overexpression [ 42 , 79 ].…”
Section: Colistin Resistance Mechanisms In K Pneumoniaementioning
confidence: 99%